Antiplatelet Use and Ischemic Stroke Risk in Minor Stroke or Transient Ischemic Attack: A Post Hoc Analysis of the POINT Trial. Issue 12 (12th October 2021) - Anadani, Mohammad; de Havenon, Adam; Henninger, Nils; Kuohn, Lindsey; Mac Grory, Brian; Furie, Karen L.; Kim, Anthony S.; Easton, J. Donald; Johnston, S. Claiborne; Yaghi, Shadi
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Dual antiplatelet therapy has been shown to reduce the risk of recurrent stroke in patients with minor stroke or transient ischemic attack. However, whether the effect of dual antiplatelet therapy is modified by pretreatment antiplatelet status is unclear. Methods: This is a post hoc analysis of the POINT trial (Platelet-Oriented Inhibition in New TIA and Minor Ischemic Stroke). Patients were divided into 2 groups based on pretreatment antiplatelet use. The primary outcome was ischemic stroke within 90 days of randomization. Results: We included 4881 patients of whom 41% belonged to the no pretreatment antiplatelet. Ischemic stroke occurred in 6% and 5% in the antiplatelet pretreatment and no antiplatelet pretreatment, respectively. Antiplatelet pretreatment was not associated with the risk of ischemic stroke (adjusted hazard ratio, 1.05 [95% CI, 0.81–137]) or risk of major hemorrhage (hazard ratio, 1.10 [95% CI, 0.55–2.21]; P =0.794). The effect of dual antiplatelet therapy on recurrent ischemic stroke risk was not different in patients who were on antiplatelet before randomization (adjusted hazard ratio, 0.69 [95% CI, 0.50–0.94]) as opposed to those who were not (adjusted hazard ratio, 0.75 [95% CI, 0.50–1.12]), P for interaction = 0.685. Conclusions: In patients with minor stroke and high-risk transient ischemic attack, dual antiplatelet therapy reduces the risk of ischemic stroke regardless of premorbid antiplatelet use.